Analisis Faktor Penyebab Stres Pada Pekerja Jalur di Pabrik Fabrikasi Baja II PT Wijaya Karya Industri & Konstruksi Tahun 2019 - Sarah Kilbaren; Elwindra Elwindra (Jurnal Persada Husada Indonesia, 2020)
Job stress is a feeling of stress experienced by employees in dealing with work. The existence of demands on the workforce such as in terms of mastery of new technology, restrictions or tighter times, changes in demands on work results, as well as changes in work regulations, can lead to a situation that pressures employees. The study aims to analyze the factors that cause stress on the lane workers at Baja Fabrication Plant II PT Wijaya Karya Industrial & Construction. This study uses a qualitative design with the research approach used is phenomenology. The nature of the production process that occurs in the construction industry makes construction work dangerous and full of risks that can cause stress. The data collection process was carried out from May to June 2019. The method used was in-depth interviews, observations, and document review, to find out the characteristics, work motivation, job satisfaction, workload, work organization, and work environment. The results showed that the characteristics of workers in the steel fabrication plant line are predominantly male, and young, the workload is felt by workers at a younger age than the elderly. Some workers feel uncomfortable working because of physical environmental factors, but some are accustomed to being used to adapt. The target work that must be completed within a certain time can be a factor causing stress on track workers, and also income that is felt to be lacking and not in accordance with workload. The results of this study are expected to be a reference and useful for further research, and are also expected to be taken into consideration for the determination of policies from the company, especially with regard to occupational safety and health.